2017
DOI: 10.3390/f8120474
|View full text |Cite
|
Sign up to set email alerts
|

Physical Conditions Regulate the Fungal to Bacterial Ratios of a Tropical Suspended Soil

Abstract: Abstract:As a source of 'suspended soils', epiphytes contribute large amounts of organic matter to the canopy of tropical rain forests. Microbes associated with epiphytes are responsible for much of the nutrient cycling taking place in rain forest canopies. However, soils suspended far above the ground in living organisms differ from soil on the forest floor, and traditional predictors of soil microbial community composition and functioning (nutrient availability and the activity of soil organisms) are likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Gram positive and gram negative bacteria had the highest relative importance in Asplenium nidus, A. phyllitidis, and A. serratum, ranging from 19 to 21%, followed by fungi (5-11%) and actinomycetes (4%) inferred from the analysis of phospholipid fatty acid profiles (Donald et al 2017(Donald et al , 2020. A comparison between A. phyllitidis and A. serratum (from Borneo and Amazonia respectively) show they have the same groups of microorganisms but different compositions, with a greater abundance of fungi in the drier conditions of Borneo (Donald et al 2017(Donald et al , 2020. Fungi are more likely to succeed in the canopy of dry forests because they are able to transfer water through their hyphae (Guhr et al 2016;Donald et al 2017).…”
Section: Influence Of Trash-basket Epiphytes On Forest Biodiversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Gram positive and gram negative bacteria had the highest relative importance in Asplenium nidus, A. phyllitidis, and A. serratum, ranging from 19 to 21%, followed by fungi (5-11%) and actinomycetes (4%) inferred from the analysis of phospholipid fatty acid profiles (Donald et al 2017(Donald et al , 2020. A comparison between A. phyllitidis and A. serratum (from Borneo and Amazonia respectively) show they have the same groups of microorganisms but different compositions, with a greater abundance of fungi in the drier conditions of Borneo (Donald et al 2017(Donald et al , 2020. Fungi are more likely to succeed in the canopy of dry forests because they are able to transfer water through their hyphae (Guhr et al 2016;Donald et al 2017).…”
Section: Influence Of Trash-basket Epiphytes On Forest Biodiversitymentioning
confidence: 99%
“…A comparison between A. phyllitidis and A. serratum (from Borneo and Amazonia respectively) show they have the same groups of microorganisms but different compositions, with a greater abundance of fungi in the drier conditions of Borneo (Donald et al 2017(Donald et al , 2020. Fungi are more likely to succeed in the canopy of dry forests because they are able to transfer water through their hyphae (Guhr et al 2016;Donald et al 2017). Fungi also form litter-trapping networks on their own (Snaddon et al 2012).…”
Section: Influence Of Trash-basket Epiphytes On Forest Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, certain members of the Bromeliaceae family form water and litter-storing phytotelmata and take up nutrients through leaf-absorbing trichomes [29,34,35], whilst Asplenium ferns intercept falling leaf litter, which is then stored as organic matter adjacent to the roots [27,36]. For both epiphytes, this accumulation of leaf litter leads to the formation of organic matter or epiphyte-associated soils that harbor characteristic levels of microbial diversity [37,38]. The extent of this harboring is not well understood, in part due to the difficulty of sampling this habitat, but also due to our inability to characterize the entire spectrum of the metabolome.…”
Section: Introductionmentioning
confidence: 99%
“…Tree diversity has been shown to influence soil heterogeneity in tropical forests [48], whereby the impacts of differences in litter species composition and their released leachate shapes both forest floor traits [49,50] and suspended canopy soils [24]. Thus, changes in soil traits and contrasting microbe community composition, nutrient status, and enzyme content of forest floor and suspended soils have been observed to depend on tree species [26,38,51]. Canopy soils have higher concentrations of organic matter than ground m. A recent study in a tropical mountain rainforest in Costa Rica revealed that canopy soils harbor very different symbiotic and fungi communities compared to ground soils and have much more enzymatic activity [26].…”
Section: Introductionmentioning
confidence: 99%